Technoeconomic Analysis of Prospects of Use of Organic Coal-Water Fuels of Various Component Compositions; Chemical and Petroleum Engineering; Vol. 53, iss. 3-4 - Dmitrienko M. A. Margarita Aleksandrovna (2017, 2017)
Title screen